(untitled) (International Journal of Engineering Sciences & Management Research, 2016)
The chief function of a building is to provide comfortable indoor environment to the occupants. Thus, the focus of energy conservation practices is to optimize energy performance of a building and reducing dependence on energy guzzling electromagnetic devices without compromising comfort of inhabitants. Energy consumption in a building is mainly in Heating, Ventilation, Air conditioning (HVAC), lighting, lifts, water pumps, running domestic appliances, operating electronic gadgets and due to losses in local transmission. The building energy consumption which is mainly in form of electricity is ever increasing and with rapid urbanization, it is bound to accelerate to unprecedented levels unless corrective measures are taken to reduce dependence on exhaustible energy sources.